231k views
4 votes
[6 × (4 − 2) + (21 × 2/3 + 1)] ÷ 3²
If you can, please explain.

2 Answers

4 votes

Answer:

3

Explanation:

[6 x (4 - 2) + (21 x 2/3 + 1)] ÷ 3^2

[6 x 2 + (21 x 2/3 + 1)] ÷ 3^2

21 x 2/3 = 42/3 = 14

[6 x 2 + (14 + 1)] ÷ 3^2

[6 x 2 + 15] ÷ 3^2

[12 + 15] ÷ 3^2

27 ÷ 3^2

3 x 3 = 9

27 ÷ 9 = 3

User Manukv
by
5.1k points
4 votes

Answer:

3

Explanation:

Use BODMAS

solve the ones in brackets first followed by multiplication/division based on the order given

User Freshest
by
5.5k points